Enhancing Arabic Morphology Learning via Jigsaw: An Experimental Study in a Islamic Boarding School - Habib, Moh. Tohiri (Institut Agama Islam Negeri Palangka Raya, 2025)
Arabic morphology (Sharaf) is essential in mastering the Arabic language, yet traditional rote-learning methods in Pesantren often lead to passive learning and low retention. This study explores the effectiveness of the Jigsaw Method a cooperative learning strategy in improving Sharaf learning at Madrasah Tsanawiyyah Darullughah Wadda’wah, involving 60 students aged 13–15. Using a qualitative approach, data were gathered through classroom observations, interviews, and focus group discussions. The findings reveal that the Jigsaw Method significantly enhanced student engagement, motivation, comprehension, and confidence in peer-based learning. It also reduced anxiety and encouraged active participation. Despite these benefits, challenges such as vocabulary retention and the need for structured implementation remain. This study addresses a pedagogical gap in Sharaf instruction within Pesantren and supports the value of cooperative learning models in Arabic language education. Further research is recommended to assess long-term impacts and extend the method’s application to areas like Nahwu and Balaghah.